Moral Thinking and Its Relationship to Professional Competence among History Teachers - Jawad, Amal Nouri (Zanco Journal of Human Sciences, 2025)
The professional ethical thinking of history teachers, by the nature of their work, includes their ethical thinking in their relationship with students, and their ethical values ​​in their relationship with their colleagues. Since female student teachers cannot judge all aspects of the professional ethical thinking of female history teachers, the researcher limited the current study to addressing ethical thinking related to teaching inside the classroom and the course taught to female student teachers, and its relationship with professional competence. Given the growing international interest in the central importance of ethical values ​​in teaching, empirical studies that explore the relationships between teachers’ ethical thinking and other aspects of their competence are conspicuously absent. Such studies can serve to justify certain values ​​as more appropriate for teachers than others, and can benefit the design of relevant components in teacher education (Cummings et al., 2007, Willemse et al., 2008). The question of how to justify values ​​can be viewed as a question for educational philosophers or policy makers, not for practitioners, but the fruits of any values ​​in teaching practices ultimately depend on the ability of teachers to Teachers need to reflect on and internalize these values ​​in their lives. (Veugelers & Vedder, 2003) Carr (1993a, pp. 20-21) suggested that the relationship between the practical and the ethical needs to be explored in our thinking about the nature of teachers' professional knowledge and behavior. Colnerud (2006, pp. 384-385) suggested that teachers' ethical roles need to be investigated in relation to their responsibility to provide students with cognitive challenges that are valuable to them.